2023
DOI: 10.18063/esp.v7.i2.1501
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking Customer Satisfaction of Halal Restaurant in South Korea through Online Review Analysis

Abstract: The purpose of this study is to examine customer satisfaction of halal restaurants that have received halal certification from the Korea Muslim Federation (KMF). A total of 1,544 reviews from 11 halal-certified restaurants in South Korea were collected from Google reviews using SCTM 3.0 (Smart Crawling and Text Mining). UCINET 6.0 is used to analyze the network centrality and perform CONCOR analysis. This study quantitatively identified the relationship among five dimensions: halal cuisine, Islamic dining, foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
1
0
0
Order By: Relevance
“…When analyzing results derived from text mining, especially subjective data like user opinions, capturing the entirety of influential factors becomes challenging. Previous research has also indicated that in such scenarios, the R² value might be on the lower side reinforcing the findings of this study (Handani & Kim, 2023;Kim & Noh, 2019).…”
Section: B Statistical Analysissupporting
confidence: 90%
“…When analyzing results derived from text mining, especially subjective data like user opinions, capturing the entirety of influential factors becomes challenging. Previous research has also indicated that in such scenarios, the R² value might be on the lower side reinforcing the findings of this study (Handani & Kim, 2023;Kim & Noh, 2019).…”
Section: B Statistical Analysissupporting
confidence: 90%
“…Essentially, satisfaction refers to the enjoyment vacationers seek from the goods, services, and locations they visit. In light of that, tourism satisfaction is likely to be influenced by a variety of factors, such as service quality and customer satisfaction [21] . As a result, pleased visitors are expected to return and recommend the place to others, while unsatisfied visitors do not expect to return or make additional purchases, which results in a negative outcome.…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…By comparison, 3798 reviews are from pre-COVID 19 and 5683 reviews are from post-COVID 19. Data were analyzed quantitatively using exploratory factor analysis and regression analysis using SPSS 27 to determine the data for this study [5,33] . The research process is shown in Figure 1.…”
Section: Data Collectionmentioning
confidence: 99%
“…On the other hand, the dependent variable in this study was customer satisfaction. This was derived from ratings found in online reviews, which provide a direct insight into customers' experiences during their stay at the hotel [5,8] . Online reviews serve as a rich source of user-generated content, often offering detailed perspectives on various aspects of the customer experience.…”
Section: Variables and Measurementmentioning
confidence: 99%
See 1 more Smart Citation